A case report of childhood cutaneous cartilaginous tumor located in the neck - He, Yijia; Wu, Zhuochen; Zhu, Qing; Qi, Jinxu; Xuan, Xiaomei; Zhang, Guoqiang (Frontiers in Pediatrics, 2025)
BackgroundCutaneous Cartilaginous Tumor, also known as Chondromacutis, is a rare benign tumour of the skin that develops in the hands and feet. It is extremely rare to find lesions located in the neck. It typically occurs in adults aged 30–60 years and is rare in children, with no gender predilection. The disease may have a mesenchymal cellular origin. The tumour is located in the dermis and may involve subcutaneous tissue.CaseIn this paper, we report a case of a 6-year-old child. The child was born with a skin-coloured hemispherical mass with a smooth surface on the right side of her neck. The swelling gradually increased in size and she presented to the dermatology department. Histopathological examination confirmed Cutaneous Cartilaginous Tumor.ConclusionReports of Cutaneous Cartilaginous Tumor located in the neck of children are extremely rare. The case of Cutaneous Cartilaginous Tumor in the right neck of a 6-year-old child reported in this study supplements the clinical data of this tumor in special populations and special locations, provides a typical case reference for clinical identification of such rare benign tumors, and also accumulates basic data for existing literature and subsequent related research.